TRACE MATRIKS FLDcircr BENTUK KHUSUS BERPANGKAT DUA - Ade Novia Rahma; Sri Sukmawati; Rahmawati Rahmawati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Tracking the matrix is ​​the sum of the elements on the main diagonal of the matrix. This study aims to determine the Trace of a specially shaped quadratic FLDcircr matrix. In determining the Trace of a squared FLDcircr matrix, there are a number of steps to be take. First determine the special shape of the to 8x8 FLDcircr,  matrix so that the general shape of FLDcircr, is formed to form a special quadratic.Furthermore, from the equations obtained, we can determine the Trace of the FLDcircr matrix in the form of a special quadratic order of the matrix  to , Having obtained the general form of Trace from the FLDcircr matrix, we can prove it by direct proof